Grinding Temperature with Nanoparticle Jet Minimum Quantity Lubrication - Hou, Yali; Li, Changhe; Zhang, Dongkun; Jia, Dongzhou; Wang, Sheng (Recent Patents on Mechanical Engineering, 2014)
In recent years, a large number of patents have been devoted to developing minimum quantity lubrication (MQL) grinding techniques for environment friendly, energy saving, and cost-effective grinding fluid alternatives. One patent involves the nanoparticle jet flow in the MQL of grinding lubricant supply systems. An MQL grinding lubricant is prepared by adding nanoscale solid particles into a degradable grinding liquid. The lubricant is turned into pulse liquid drops with fixed pressure, variable pulse frequency, and invariant liquid drop diameter. The pulse liquid drops are sprayed into a grinding region in the form of jet flow by an air-isolating layer formed by high-pressure gas. The system has the advantages of MQL technology, has high cooling performance and excellent tribological characteristic, and plays an important role in effectively avoiding grinding burn, thus enhancing the surface quality of the workpiece and realizing an efficient, low consumption, environment friendly, economic, low carbon, and clean production. The temperature field model of surface grinding with a nanoparticle jet flow of MQL and the proportionality coefficient model of the energy input workpiece were established. The surface grinding temperature fields of 45 Steel and 2Cr13 were numerically simulated. Results show that the surface temperature of the workpiece is significantly higher than the subsurface temperature, thus presenting a relatively large temperature gradient along the direction of workpiece thickness. Grinding depth significantly affects grinding temperature. The values of grinding temperature increase with increasing cutting depth. The uniform distribution rules of the 2Cr13 temperature field are observed in four cooling and lubrication approaches: dry grinding, flood grinding, MQL, and nanoparticle MQL jet flow. Experiments are conducted to verify the simulation results. The results show that grinding temperature increases significantly with the increasing peripheral velocity of the grinding wheel. Furthermore, the movement speed of a workpiece is inversely proportional to the grinding temperature and a larger cutting depth contributes to higher grinding temperature. These results are consistent with theoretical analysis and show the effectiveness of the simulation method.
Keywords: minimum quantity lubrication (MQL)